1998
DOI: 10.1021/jo9802170
|View full text |Cite
|
Sign up to set email alerts
|

Tandem Inter [4 + 2]/Intra [3 + 2] Cycloadditions of Nitroalkenes. Asymmetric Synthesis of Highly Functionalized Aminocyclopentanes Using the Bridged Mode (β-Tether) Process

Abstract: An asymmetric, tandem inter [4 + 2]/intra [3 + 2] bridged mode (beta-tether) cycloaddition of nitroalkenes has been developed. This new sequence involves the Lewis acid-promoted [4 + 2] cycloaddition of nitro olefins with enantiopure 1-alkoxy-1,4-dienes. The resulting nitronates, bearing a C(5) tethered dipolarophile, undergo thermal, intramolecular [3 + 2] cycloaddition to afford stable tricyclic nitroso acetals, which can be subsequently reduced to provide interesting aminocyclopentanes. Thus, in three steps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
1
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 78 publications
0
15
1
1
Order By: Relevance
“…While the C 6 −C 7 double bond of DNBF behaves as the dienophile in the condensation leading to 6 , it is part of the O 6 −N 6 −C 6 −C 7 fragment, which acts as a heterodienic moiety in the condensation pathway leading to 7 . The formation of 6 and 7 highlights the ambident Diels−Alder reactivity of DNBF while adding to the evidence that nitrobenzofuroxans are 10π-electron heteroaromatics of low resonance energy. 1a,5d,e In this regard, the behavior of DNBF may be compared to that of nitroalkenes, which are known to react as dienophiles or heterodienes, depending upon the experimental conditions and the systems at hand. In particular, Denmark and co-workers have recently reported the formation of a number of dihydrooxazine N -oxide structures from Lewis-acid promoted [4 + 2] cycloadditions of nitroalkenes with various dienophiles, including cyclopentadiene. , …”
mentioning
confidence: 99%
“…While the C 6 −C 7 double bond of DNBF behaves as the dienophile in the condensation leading to 6 , it is part of the O 6 −N 6 −C 6 −C 7 fragment, which acts as a heterodienic moiety in the condensation pathway leading to 7 . The formation of 6 and 7 highlights the ambident Diels−Alder reactivity of DNBF while adding to the evidence that nitrobenzofuroxans are 10π-electron heteroaromatics of low resonance energy. 1a,5d,e In this regard, the behavior of DNBF may be compared to that of nitroalkenes, which are known to react as dienophiles or heterodienes, depending upon the experimental conditions and the systems at hand. In particular, Denmark and co-workers have recently reported the formation of a number of dihydrooxazine N -oxide structures from Lewis-acid promoted [4 + 2] cycloadditions of nitroalkenes with various dienophiles, including cyclopentadiene. , …”
mentioning
confidence: 99%
“…In addition, we have observed that the reaction selectivity has also been dramatically affected [22] [31]. With SnCl 4 , the [4 2] reaction generally proceeds through a ul-type transition structure (exo with respect to the OR group in the vinyl ether).…”
Section: Discussion ± 41 [4 2] Cycloadditionmentioning
confidence: 99%
“…Thus, lactam 8b was synthesized as reported, 1a with slight modification: The S-enantiomer of 1-(2,4,6-triisopropylphenyl)ethanol ( 5), chosen to gain access to the desired antipodal series, was converted in high yield to the dichloroenol ether 6, which in turn was treated with 2 equivalents of n-BuLi, followed by allyl iodide, to yield ynol ether 7a (Scheme 2). Partial reduction of the triple bond was performed with DIBAL-H in toluene at 50°C, 6 instead of by catalytic hydrogenation with the Lindlar catalyst, to give enol ether 7b, now free of the 10-20% of over-reduced material previously observed on hydrogenation. 1a Diastereoface-selective cycloaddition of dichloroketene to 7b, followed by Beckmann ring expansion and dechlorination, then afforded lactam 8b in 38% overall yield for the five steps (82%/step).…”
Section: Methodsmentioning
confidence: 99%